AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN KOMPONEN ELEKTRONIKA DASAR BERBASIS ANDROID - Kustrianugraha, Afri Fajar; Wibowo, Adityo Permana (Politeknik Bisnis Indonesia, 2023)
Technological advances in the field of electronics require students and teachers to understand and recognize components related to electronics. Currently, explanations and learning materials for electronic components still rely on books or exercise modules which are basically difficult to understand. As a result, students feel bored and ultimately fail to achieve the expected competencies. The purpose of this research is to create and build a mobile application for Android, which aims to design an Android-based application that utilizes Augmented Reality to introduce basic electronic components using a marker-based tracking method. This makes learning the introduction of electronic components more interesting. This research uses several tools such as Unity, Blender, Vuforia, and ARToolkit. The research methodology used is MDLC (Multimedia Development Life Cycle), and for the testing method using black box testing shows the features in the application are free from errors, and Usability testing using a questionnaire with 95% ease of use and 90% usability aspects. This application can be classified as having undergone testing within the